La scienza costituzionale canonica nella codificazione del 1917 (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Panoramica della scienza costituzionale agli albori del secolo - 2. L’impronta costituzionalistica insita nel metodo codiciale - 3. La prospettiva materiale o oggettiva della “idea costituzionale” soggiacente al CIC 17 - 4. La prospettiva formale della strutturazione societaria emergente dal CIC - 5. Il centralismo - 6. L’autoritarismo - 7. Il clericalismo - 8. Valutazione di sintesi dell’ottica costituzionalistica codiciale.The canonical constitutional science in the didification of 1917ABSTRACT: Presuming a panoramic summary of constitutional science within canonical thought in the period immediately prior to the Pio-Benedictine Code, this author’s contribution seeks to delineate the material and formal perspectives of the cornerstones of the canonical system that have been assumed by the Legislator. The method of a Code entails, first of all, a complete and organic systematization of the law of the Church. The “constitutional idea” underlying the CIC appears, though, to be firmly anchored to the Church’s hierarchical constitution. As we know, the common figure of the faithful; the active role of the laity; the communal structure of the People of God; the original nature of the episcopacy and the effects of collegiality; the significance of the particular Church; etc. (which will overwhelmingly emerge in the Vatican Council II), are considerably obscured, if not altogether absent, in the prior structure of the Code. This contribution demonstrates the manner in which centralism, authoritarism and clericalism emerge as critical points of orientation in the “positivation” of the canonical system, taking into consideration its logical and conceptual structure without descending into a specific analysis of canons and institutions. While the limitations examined reflect the state of theological and canonical speculation of the time, the new legislative form has ensured the presence of order and balance in the system, heralding its maturation and development.